Determination of heparin-induced IgG antibody in heparin-induced thrombocytopenia type II - Wang, Lianchun; Huhle, Günter; Malsch, Reinhard; Hoffmann, Ursula; Song, Xuehong; Harenberg, Job (European journal of clinical investigation, 1999)
Background Heparin-induced thrombocytopenia is a relatively uncommon but severe side-effect of heparin therapy. Heparin-induced IgG antibody has been elucidated to be the main isotype and the most pathogenic antibody in the pathophysiology. As affected patients are at high risk of developing thrombotic events, confirmation of the clinical diagnosis and avoidance of heparin re-exposure are important and desirable. Materials and methods In the present study, heparin-induced IgG was measured by the binding of neoantigens, which were prepared by incubating FITC-heparin with platelet factor 4 present in normal serum. The cross-reactivities of heparin-induced IgG with low-molecular-weight heparin and danaparoid were analysed by competitive binding. Results A total of 81 clinically suspected heparin-induced thrombocytopenia type II patients were analysed. Thirty-seven of 38 heparin-induced thrombocytopenia type II patients, in whom thromboembolism was confirmed by objective methods, had elevated relative fluorescence intensity ratios (patient normal control) and 36 had positive heparin-induced platelet activation results. The prevalence of heparin-induced IgG in heparin-induced thrombocytopenia type II patients was 97.4%. Positive heparin-induced IgG results were: 0/319 healthy volunteers, 0/38 other thrombo-cytopenia and 2/56 heparin/low-molecular-weight heparin-receiving patients without thrombocytopenia, 2/41 hyperbilirubinaemic patients and 2/50 hyperlipidaemic patients. A small amount of cross-reaction assays showed similar results as obtained in heparin-induced platelet activation. Conclusion Our results suggest that a very high frequency of heparin-induced IgG in heparin-induced thrombocytopenia type II patients can be detected using a novel antigen assay. The rapid determination of pathogenic heparin-induced IgG may be a useful tool for the rapid diagnosis of heparin-induced thrombocytopenia type II that could facilitate further management of the patients.
Gesehen am 24.05.2022